الدراسة البنيوية والكهربائية والضوئية لأكسيد القصدير المطعم بلحديد - حسيبة, حروشي; يمينة, مردف (universty of elouedجامعة الوادي, 2020)
تم الاهتمام خلال هذا العمل بدراسة كل من الخصائص البنيوية ،الكهربائية والضوئية لأغشية أكسيد القصدير النقي (SnO2) والمطعم بالحديد (Fe) بنسب (0.2-1)%، وذلك إنطلاقا من كلوريد القصدير(SnCl2) وكلوريد الحديد (FeCl3) يتم ترسيب المحلول على ركائز زجاجية تحت درجة حرارة 480C° لمدة 4 دقائق وذلك من خلال تقنية الرش بالانحلال الحراري . أظهر إنعراج الأشعة السينية أن لأغشية أكسيد القصدير المطعم بالحديد بنية متعدد التبلور رباعي الزوايا وتأخذ الإتجاه التفضيلي (211). أبدت النفاذية الضوئية تزايدا من 82%إلى 94% ، أما المقاومة السطحية فقد شهدت إرتفاعا من( 652Ω) عند نسبة التطعيم 0.8% . تتغير قيم الفاصل الطاقي وفقا لنسب التطعيم بالحديد ليأخذ القيم من 3.483 eVحتى 3.801 eV "bstract In this work, We studied structural, electrical and optical properties, and characterization of undoped tin oxide (SnO2) and iron (Fe) doped (SnO2) thin films , Which have been deposited from tin chloride (SnCl2) and iron chloride (FeCl3) onto glass substrates by spray pyrolysis technique. Samples were deposited for4 minutes at the substrate temperature of 480¬C°. The doping concentration of (Fe) was varied from 0.2 to 1 (%) in solution . X-ray diffraction (XRD) has shown polycrystalline structure according to Tetragonal , Rutile (SnO2) structure with (211) as preferential orientation for iron (Fe) doped (SnO2) thin films. The optical transmittance of (SnO2:Fe) films in visible spectra increases from 82% to 94%, The sheet resistance (Rsh) varied from 34.44) Ω) to652) Ω) for Fe-doping in the range of 0.8%.The optical band gap (Eg) increased from (3.483eV) to (3.801eV) with increasing of the concentration of iron Fer (Fe) dopants. "
مذكرة تخرج ماستر فيزياء
Keywords: أكسيد القصدير (SnO2) ، الرش بالإنحلال الحراري ، الأغشية الرقيقة ،الحديد(Fe) ،إنعراج الأشعة السينية ،الفاصل الطاقي Eg، المقاومة الكهربائية السطحية Rsh.; Tin in oxide(SnO2), soray pyrolysis, thin fulms, iron(Fe), x-raydiffraction(XRD), band gap(Eg), the sheet resistance (Rsh)